Melamine-titanium carbide-cobalt-nickel composite foam material as well as preparation method and application thereof
By combining titanium carbide and cobalt nickel metal particles on the surface of melamine foam, melamine-titanium carbide@cobalt nickel composite foam material was prepared, which solved the problems of single absorbent materials, small reflection loss and narrow absorption bandwidth, and achieved efficient preparation and excellent performance of versatile materials.
Patent Information
- Application Number
- CN202510088117.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing absorbent materials are single, have small reflection loss and narrow absorption bandwidth, making it difficult to have versatile abilities such as electromagnetic wave absorption, photothermal conversion and antibacterial properties.
The melamine-titanium carbide@cobalt-nickel composite foam material is used to combine titanium carbide and cobalt-nickel metal particles on the surface of the three-dimensional melamine foam through vacuum impregnation and electrostatic self-assembly to form a multi-component lightweight broadband composite wave absorbing foam material.
实现了对电磁波的有效吸收,具有卓越的光热转换能力和优异的抗菌性能,反射损耗强,微波吸收频带宽广,适用于无线通信设备、雷达探测及隐身技术等领域。
Smart Images

Figure CN119529379A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and particularly relates to a melamine-titanium carbide@cobalt-nickel composite foam material and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern science and technology, especially in the fields of aerospace, electronic information, biomedicine, etc., the demand for high-performance electromagnetic wave absorbing materials is growing. These materials should not only have excellent electromagnetic wave absorption capabilities to solve the increasingly serious problems of electromagnetic interference and electromagnetic radiation, but also take into account the characteristics of lightweight, environmental friendliness and multifunctionality. In recent years, new composite absorbing materials with both photothermal conversion and antibacterial functions have become a research hotspot. While improving the performance of electronic equipment, they can also effectively meet the needs of photothermal therapy and antibacterial protection. 3 C 2 T X As an emerging two-dimensional material, it has shown great potential in the field of electromagnetic wave absorption due to its unique physical and chemical properties, such as high specific surface area, good conductivity and adjustable surface chemical properties. By combining it with a melamine foam matrix, not only can the dielectric properties of the material be optimized, but also the electromagnetic wave absorption capacity can be enhanced through the interfacial polarization effect. In addition, the three-dimensional pore structure of melamine foam and Ti 3 C 2 T X The surface plasmon resonance effect of Ti leads to a higher photothermal conversion efficiency, which provides a basis for the photothermal and antibacterial applications of materials. 3 C 2 T X There are problems such as single loss, weak absorption intensity, and poor impedance matching, which need to be further improved. As a typical magnetic material, cobalt-nickel alloy has good magnetic loss characteristics and can effectively absorb and dissipate electromagnetic wave energy.
[0003] By introducing magnetic materials such as cobalt and nickel, a multiphase heterogeneous structure can be formed. The synergistic effect of magnetic loss and dielectric loss can further improve the electromagnetic wave absorption performance of the material. 3 C 2 T xThe 2D / 0D / 1D structured MXene-CoNi@NCNT composite material obtained by in-situ growth of zero-dimensional CoNi nanoalloy encapsulated one-dimensional nitrogen-doped carbon nanotubes has a special structure and the synergistic effect of dielectric / magnetic loss, which optimizes impedance matching and enhances attenuation capability. When the coating thickness is 2.1 mm, the optimal reflection loss value reaches –55.3 dB (J. Cheng, B. Liu, Y. Wang, H.Zhao, Y. Wang. Journal of Materials Science&Technology, 2022, 30(3): 343-351.). The prior art also discloses a method of assembling magnetized Ni flowers and Ti on the surface of melamine foam. 3 C 2 T X The Ni-MXene / MF composite foam obtained by MXene has an optimal reflection loss value of -62.7 dB when the matching thickness is 2.0 mm, and an effective absorption bandwidth of 6.88 GHz at 1.8 mm (H. Cheng, Y. Pan, X. Wang, et al. Nano-Micro Lett, 2022, 130: 157-165.). Existing preparation technologies are mostly focused on the synthesis of single functional materials, while for the preparation of composite materials with multiple functions (such as electromagnetic wave absorption, photothermal conversion and antibacterial properties), there are still problems such as complex synthesis process, difficult to balance material properties, and high cost. Therefore, developing a simple, efficient and environmentally friendly preparation method to prepare a multifunctional composite absorbing material with excellent performance and stable structure is of great significance for promoting the multifunctionalization of electromagnetic wave absorbing materials. Summary of the invention
[0004] The present invention aims to solve the problems of single existing absorbing materials, small reflection loss, narrow absorption bandwidth, etc., and provides a preparation method and application of a melamine-titanium carbide @ cobalt nickel composite foam material with both photothermal antibacterial and absorbing properties. The melamine-titanium carbide @ cobalt nickel composite foam material is a multi-component lightweight broadband composite absorbing foam material formed by compounding high dielectric loss and strong magnetic loss materials with melamine foam. The preparation process is simple, efficient and low-cost.
[0005] The present invention uses three-dimensional melamine foam as a matrix, and composites titanium carbide and cobalt-nickel metal particles on its surface through vacuum impregnation and electrostatic self-assembly processes to obtain a melamine-titanium carbide @ cobalt-nickel composite foam material. The melamine-titanium carbide @ cobalt-nickel composite foam material prepared by the present invention has the advantages of multiple loss mechanisms, strong reflection loss and wide microwave absorption bandwidth, and can achieve effective absorption of electromagnetic waves.
[0006] To achieve the above technical objectives, the technical solution of the present invention is as follows: A method for preparing a melamine-titanium carbide@cobalt-nickel composite foam material comprises the following steps: S1, cleaning and pre-treating the melamine foam, then placing the treated melamine foam in a Tris buffer containing dopamine hydrochloride (PDA) and stirring it, then washing it with deionized water for multiple times, and drying it for later use; S2, ultrasonically treating the cobalt-nickel particles in a hexadecyltrimethylammonium bromide (CTAB) solution for 30 min, and drying to obtain a cobalt-nickel particle (CTAB) material, stirring the titanium carbide powder and the cobalt-nickel particles (CTAB) in deionized water, ultrasonically treating for 30 min until uniform, and drying to obtain a titanium carbide@cobalt-nickel composite material; S3. Disperse the titanium carbide @ cobalt nickel composite material obtained in S2 in deionized water to obtain a titanium carbide @ cobalt nickel solution, vacuum impregnate the melamine foam obtained in S1 in the titanium carbide @ cobalt nickel solution for 2 h, and dry to obtain a melamine-titanium carbide @ cobalt nickel composite foam material.
[0007] Furthermore, the concentration of dopamine hydrochloride (PDA) in Tris buffer is 1-5 mg / mL.
[0008] Furthermore, the concentration of the cetyltrimethylammonium bromide (CTAB) solution is 1-5 mg / mL.
[0009] In the present invention, titanium carbide (TiC) and cobalt-nickel particles are first compounded and then loaded onto melamine foam (MF), which has the following advantages compared to the prior art method of directly loading titanium carbide and cobalt-nickel particles onto melamine in steps: (1) During the composite process, titanium carbide and cobalt-nickel particles have been fully mixed and dispersed, so when the composite material is loaded onto melamine foam, it can be distributed more evenly. 3 C 2 If separate cobalt nickel and titanium carbide particles are directly loaded onto melamine foam, particle aggregation may occur, resulting in uneven material distribution and affecting the performance of the composite material, especially the mechanical properties, thermal properties and electromagnetic absorption properties.
[0010] (2) Improve interface bonding strength: By first compounding, a certain binding force has been formed between the cobalt-nickel particles and the titanium carbide particles through physical adsorption or chemical interaction. In this way, the interfacial bonding force of the composite material will be enhanced, reducing the separation or shedding of the cobalt-nickel and titanium carbide particles that may occur during the loading process. If loaded directly, the binding force between cobalt-nickel and titanium carbide is weak, which may cause the particles to be unstable on the foam surface, especially when the external environment changes, the particles are easy to fall off or disperse unevenly.
[0011] (3) Improve the stability and controllability of composite materials: By compounding first, the composition and structure of the composite material are easier to control, ensuring that the composite material loaded on the foam surface is already stable and well-proportioned, thereby improving the stability of the final composite material. Direct loading may lead to incomplete interaction between materials, especially when the particles are not fully dispersed or there is no good surface modification, the surface of the foam may have uneven physical or chemical bonding, resulting in instability of the composite.
[0012] Disadvantages that can be overcome (1) Uneven particle aggregation and dispersion: Compounding before loading can overcome the problem of particle aggregation that may occur during direct single loading. Through compounding, titanium carbide and cobalt nickel particles are evenly distributed, thus avoiding the situation in which particles aggregate on the foam surface due to poor dispersion during direct loading.
[0013] (2) Interface instability problem: If cobalt nickel and titanium carbide are directly loaded onto melamine foam separately, the interfacial bonding between the particles and the foam may be weak. By compounding first, the bonding between the particles can be improved during the compounding process, the interfacial stability of the final composite material can be enhanced, and the risk of particle shedding or material delamination can be reduced.
[0014] (3) The performance of composite materials is unstable: Composite material loaded on melamine foam has good stability and avoids the problem of inconsistent performance due to unstable or uneven material distribution during single loading. In the case of direct loading, the cobalt nickel and titanium carbide particles may not be completely evenly distributed, resulting in fluctuations or uneven performance of the composite material during use.
[0015] (3) Fragmentation or shedding during loading: Compounding before loading can avoid problems with particle shedding, fragmentation or dissolution during the loading process. In particular, during the material loading process, the structural stability of the composite material is better, which can reduce the unevenness or shedding of the composite material on the foam surface.
[0016] In summary, compared with directly loading titanium carbide and cobalt-nickel particles onto melamine foam separately, the method of first compounding and then loading can ensure more uniform particle distribution, stronger interface bonding force and higher stability, overcoming the problems of particle aggregation, uneven distribution, interface instability and so on that may occur during direct loading, thereby improving the performance and stability of the composite material.
[0017] Furthermore, the preparation method of the titanium carbide powder comprises the following steps: dissolving LiF in HCl solution, and then adding Ti 3 AlC 2 , stirred at room temperature for 24 h, repeatedly centrifuged and washed until pH = 6, collected the precipitate and dispersed it in deionized water, and titanium carbide powder was obtained after ultrasonication, centrifugation and drying for 1 h.
[0018] Furthermore, the method for preparing the cobalt-nickel particles comprises the following steps: S1, Co(NO 3 ) 2 6H 2 O and Ni (NO 3 ) 2 6H 2 O was added into methanol and stirred evenly to form solution A; dimethylimidazole and polyvinyl pyrrolidone (K30) were dissolved in methanol to form solution B; solution B was dropped into solution A and stirred for 6 hours, and CoNi-MOFs precursor was obtained after centrifugation and drying.
[0019] S2. The CoNi-MOFs precursor was pyrolyzed in an argon environment of a tubular furnace at a heating rate of 5 ° / min, kept at 800 °C-900 °C for 2 h, and cooled to obtain cobalt-nickel particles.
[0020] In the present invention, the calcination temperature cannot be lower than 800°C and cannot exceed 900°C. When the calcination temperature is lower than 800°C, the metal cobalt-nickel particles reduced from the CoNi-MOFs precursor have low crystallinity, poor dispersion between particles, and the magnetic properties and other functionalities may be significantly affected. Therefore, it is very important to ensure that the calcination temperature is higher than 800°C, which can ensure the complete reduction of the metal cobalt-nickel particles, the uniform distribution of the particles, and good performance.
[0021] Calcination temperatures exceeding 900°C can lead to excessive growth, agglomeration or sintering of metal particles, resulting in loss of surface area and functionality of the material. High temperatures may also destroy the porous structure of MOF, resulting in decreased catalytic and adsorption performance. At the same time, it may also trigger the formation of by-products, affecting material purity and performance. Therefore, calcination needs to be carried out within an appropriate temperature range to ensure the appropriate size and uniform distribution of metal particles and good material performance.
[0022] Furthermore, the mass ratio of titanium carbide and cobalt nickel particles (CTAB) is 2:1.
[0023] Furthermore, the concentration of the titanium carbide@cobalt nickel solution is 5-20 mg / mL, preferably 10 mg / mL.
[0024] The present invention also provides application of the melamine-titanium carbide@cobalt-nickel composite foam material as a light-to-heat conversion material.
[0025] The present invention also provides application of the melamine-titanium carbide@cobalt-nickel composite foam material as a photothermal antibacterial material.
[0026] The present invention also provides application of the melamine-titanium carbide@cobalt-nickel composite foam material as an electromagnetic wave absorbing material.
[0027] Compared with the prior art, the present invention has the following beneficial effects: (1) The melamine-titanium carbide@cobalt-nickel composite foam material with both photothermal antibacterial and wave-absorbing properties prepared by the present invention can effectively absorb near-infrared light and has excellent photothermal conversion capabilities. In addition, by virtue of the synergistic effect of each component, it can effectively inhibit Escherichia coli under the irradiation of near-infrared light and has excellent photothermal antibacterial properties.
[0028] (2) The present invention uses three-dimensional melamine foam as a matrix, and composites accordion-shaped titanium carbide and cobalt-nickel metal particles on its surface through vacuum impregnation and electrostatic self-assembly processes to obtain a composite foam material. The composite of multiple components and the regulation of different concentrations can effectively adjust the dielectric constant of the material, so that it has excellent impedance matching characteristics and strong loss capacity.
[0029] (3) The three-dimensional porous structure constructed by the present invention forms a cross-linked network structure inside the material, providing a conductive path. Highly conductive titanium carbide helps to enhance the conductivity loss. Cobalt-nickel particles and titanium carbide are assembled on the melamine skeleton to form a large number of heterogeneous interfaces, which not only achieves high polarization loss but also brings magnetic loss. The synergistic effect of multiple components and multiple loss mechanisms can significantly improve the absorption capacity of incident electromagnetic waves.
[0030] (4) The melamine-titanium carbide@cobalt-nickel composite foam material provided by the present invention has both photothermal antibacterial and wave-absorbing properties, and has an effective absorption bandwidth of up to 7.8 GHz at a thickness of 2.5 mm; the optimal reflection loss value is -51.4 dB. It has excellent absorption performance and lightweight and wide-bandwidth characteristics, and can be used in wireless communication equipment, radar detection, stealth technology, and other electromagnetic protection fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the melamine-titanium carbide@cobalt-nickel composite foam material of Example 2 of the present invention.
[0032] Figure 2 This is the XRD diffraction pattern of the melamine-titanium carbide@cobalt-nickel composite foam material of Example 2 of the present invention.
[0033] Figure 3 This is an electromagnetic parameter diagram of the electromagnetic wave absorbing material of Example 1 of the present invention in the 2~18 GHz frequency band.
[0034] Figure 4 This is a reflection loss diagram of the electromagnetic wave absorbing material of Example 1 of the present invention in the 2-18 GHz frequency band.
[0035] Figure 5 This is an electromagnetic parameter diagram of the electromagnetic wave absorbing material of Example 2 of the present invention in the 2~18 GHz frequency band.
[0036] Figure 6 This is a reflection loss diagram of the electromagnetic wave absorbing material of Example 2 of the present invention in the 2-18 GHz frequency band.
[0037] Figure 7 This is an electromagnetic parameter diagram of the electromagnetic wave absorbing material of Example 3 of the present invention in the 2~18 GHz frequency band.
[0038] Figure 8 This is a reflection loss diagram of the electromagnetic wave absorbing material of Example 3 of the present invention in the 2~18 GHz frequency band.
[0039] Fig. 9 This is an electromagnetic parameter diagram of the electromagnetic wave absorbing material of Comparative Example 1 of the present invention in the 2-18 GHz frequency band.
[0040] Fig.10 This is a reflection loss diagram of the electromagnetic wave absorbing material of comparative example 1 of the present invention in the 2-18 GHz frequency band.
[0041] Fig.11 This is a photothermal conversion curve diagram of the melamine-titanium carbide@cobalt-nickel composite foam material of Example 2 of the present invention at different light power densities.
[0042] Fig.12 This is a light-to-heat conversion curve of the melamine-titanium carbide@cobalt-nickel composite foam material of Example 2 of the present invention under gradually increasing light power density.
[0043] Fig.13 This is an infrared thermal imaging image of the melamine-titanium carbide@cobalt-nickel composite foam material of Example 2 of the present invention.
[0044] Fig.14 This is a diagram showing the antibacterial effect of the melamine-titanium carbide@cobalt-nickel composite foam material of Example 2 of the present invention. DETAILED DESCRIPTION
[0045] Example 1 A method for preparing a melamine-titanium carbide@cobalt-nickel composite foam material comprises the following steps: (1) Dissolve 3.6 g LiF in 9 M HCl solution and then add 2.2 g Ti 3 AlC 2 The mixture was stirred at room temperature for 24 h, washed by repeated centrifugation until pH = 6, and the precipitate was collected and dispersed in deionized water. Titanium carbide powder was obtained after ultrasonication, centrifugation and drying for 1 h.
[0046] (2) Co(NO 3 ) 2 6H 2 O and Ni (NO 3 ) 2 6H 2 O was added to 30 mL of methanol and stirred evenly to form solution A; dimethyl imidazole and polyvinyl pyrrolidone (K30) were dissolved in 20 mL of methanol to form solution B; solution B was dropped into solution A and stirred for 6 h. After centrifugation and drying, the CoNi-MOFs precursor was obtained. 3 ) 2 6H 2 O and Ni (NO 3 ) 2 6H 2 O has a molar ratio of 1:0.5~1:4, dimethylimidazole and Ni(NO 3 ) 2 ·3H 2 The mass ratio of O is 3:1.
[0047] (3) The CoNi-MOFs precursor was pyrolyzed in an argon environment of a tubular furnace at a heating rate of 5 ° / min and kept at 800 °C for 4 h. Cobalt-nickel particles were obtained after cooling.
[0048] (4) Melamine foam was ultrasonically treated with ethanol and deionized water for 30 min respectively, and the treated melamine foam was placed in 50 mL of Tris buffer containing dopamine hydrochloride (PDA) and stirred for 12 h, then washed with deionized water for several times and dried for later use. The concentration of dopamine hydrochloride (PDA) used in Tris buffer was 1-5 mg / mL.
[0049] (5) The cobalt-nickel particles were ultrasonically treated in a hexadecyltrimethylammonium bromide (CTAB) solution for 30 min and dried to obtain a cobalt-nickel particle (CTAB) material. Titanium carbide and cobalt-nickel particles (CTAB) were stirred and ultrasonicated in deionized water for 30 min until uniform, and then dried to obtain a titanium carbide@cobalt-nickel composite material. The concentration of the hexadecyltrimethylammonium bromide (CTAB) solution used was 1-5 mg / mL, and the mass ratio of titanium carbide to cobalt-nickel particles (CTAB) used was 2:1.
[0050] (6) Finally, the melamine foam in (4) was fully vacuum impregnated in a 20 mg / mL titanium carbide@cobalt nickel solution for 2 h to allow it to be completely electrostatically assembled. After drying, a melamine-titanium carbide@cobalt nickel-20 composite foam material was obtained.
[0051] Example 2 The difference between Example 2 and Example 1 is that the concentration of the titanium carbide@cobalt nickel solution is 10 mg / mL, and the other conditions are exactly the same.
[0052] Example 3 The difference between Example 3 and Example 1 is that the concentration of the titanium carbide@cobalt nickel solution is 5 mg / mL, and the other conditions are exactly the same.
[0053] Comparative Example 1 The cobalt-nickel particle composite material prepared in step (2) of Example 1 was used to make a microwave absorber, and its microwave absorption performance was tested.
[0054] The melamine-titanium carbide@cobalt-nickel composite foam material prepared in Example 2 was observed under a scanning electron microscope. Figure 1 As shown: the melamine-titanium carbide@cobalt nickel composite foam material has a three-dimensional porous structure, and titanium carbide@cobalt nickel is uniformly coated on the melamine skeleton with a diameter between 500 nm-1 μm.
[0055] The melamine-titanium carbide@cobalt-nickel composite foam material prepared in Example 2 was subjected to an X-ray diffraction (XRD) test. The results are as follows: Figure 2 As shown: the main components of the crystalline phase in the synthesized composite material are titanium carbide, cobalt (JCPDS-15-0806) and nickel (JCPDS-04-0850). XRD results show that this technical solution successfully prepares melamine-titanium carbide @ cobalt nickel-20 composite foam material.
[0056] The microwave absorption performance of the melamine-titanium carbide @ cobalt nickel composite foam material prepared in Examples 1-3 was tested: the composite foam material was used to make a microwave absorber, and the microwave absorption performance was tested. The melamine-titanium carbide @ cobalt nickel composite foam material was mixed with paraffin at a mass fraction of 40% to make a coaxial ring absorber (D 外=7 mm, d 内 =3.04 mm). The complex dielectric constant (ε) in the frequency range of 2-18 GHz was measured by Agilent Technologies N5244A electromagnetic wave vector network analyzer. r ) and complex magnetic permeability (μ r ), the reflection loss is given by ε r , μ r , the absorption frequency and the thickness of the absorber.
[0057] The dielectric constant ε of the absorber prepared in Example 1 r like Figure 3 As shown, by ε r The calculated absorption performance is as follows: Figure 4 As shown. The optimal reflection loss of the absorber at a low thickness of 1.5 mm is -20.7 dB, and the reflection loss is less than -10 dB in the range of 12.8-18.0 GHz, with an effective absorption bandwidth of 5.2 GHz; when the thickness is 2.0 mm, the minimum reflection loss is -18.5 dB, and the effective absorption bandwidth at this thickness is 3.5 GHz; when the thickness is 2.5 mm, the minimum reflection loss is -17.6 dB, and the effective absorption bandwidth at this thickness is 2.7 GHz; when the thickness of the absorber increases to 3 mm, the minimum reflection loss is -20.5 dB, and the effective absorption bandwidth is 3.5 GHz; when the thickness is 3.4 mm, the minimum reflection loss is -16.9 dB, and the effective absorption bandwidth is 1.8 GHz; when the thickness is 4.3 mm, the minimum reflection loss is -15.8 dB, and the effective absorption bandwidth is 1.3 GHz; when the thickness is 5 mm, the minimum reflection loss is -14.3 dB, and the effective absorption bandwidth is 1.0 GHz; at all thicknesses, there is an effective absorption range with reflection loss values less than -10 dB.
[0058] The dielectric constant ε of the absorber prepared in Example 2 r like Figure 5 As shown, by ε r The calculated absorption performance is as follows: Figure 6shown. The optimal reflection loss of the absorber at a thickness of 2.0 mm is -14.1 dB, and the reflection loss is less than -10 dB in the range of 14.7-18.0 GHz, with an effective absorption bandwidth of 3.3 GHz; the optimal reflection loss of the absorber at a thickness of 2.5 mm is -19.2 dB, and the reflection loss is less than -10 dB in the range of 10.2-18 GHz, with an effective absorption bandwidth of up to 7.8 GHz; when the thickness of the absorber is 3.0 mm, the optimal reflection loss is -31.5 dB, and the effective absorption bandwidth is 3.2 GHz; when the thickness is 3.4 mm, the optimal reflection loss value can reach -51.4 dB, and the effective absorption bandwidth is 3.2 GHz, which has excellent electromagnetic wave absorption performance; when the thickness is 4.3 mm, the optimal reflection loss is -38.1 dB, and the effective absorption bandwidth is 2.2 GHz; when the thickness is 5.0 mm, the optimal reflection loss is -22.3 dB, and the effective absorption bandwidth is 2.0 GHz; the reflection loss values are less than -10 at all thicknesses. dB effective absorption range.
[0059] The dielectric constant ε of the absorber prepared in Example 3 r like Figure 7 As shown, by ε r The calculated absorption performance is as follows: Figure 8 The absorber achieves the best absorption performance when the thickness is 3.0 mm, with a minimum reflection loss of -6.6 dB; when the thickness is 1.5 mm, the minimum reflection loss is -1.9 dB; when the thickness is 2.0 mm, the minimum reflection loss is -3.9 dB; when the thickness is 3.4 mm, the minimum reflection loss is -5.4 dB; when the thickness is 5.0 mm, the minimum reflection loss is -3.7 dB; at all thicknesses, there is no reflection loss value less than -10 dB, and there is no effective absorption bandwidth.
[0060] The dielectric constant ε of the absorber prepared in Comparative Example 1 r like Fig. 9 As shown, by ε r The calculated absorption performance is as follows: Fig.10The absorber can achieve the best absorption performance when the thickness is 1.1 mm, the optimal reflection loss is -11.9 dB, and the effective absorption bandwidth is 2.7 GHz at this thickness; when the thickness is 1.5 mm, the minimum reflection loss is -10.3 dB, and the effective absorption bandwidth is 1.2 GHz at this thickness; when the thickness is 2.0 mm, the minimum reflection loss is -8.4 dB; when the thickness increases to 2.5 mm, the minimum reflection loss is -7.7 dB; when the thickness is 3.4 mm, the minimum reflection loss is -6.5 dB; when the thickness is 4.3 mm, the minimum reflection loss is -6.1 dB; when the thickness is 5.0 mm, the minimum reflection loss is -5.6 dB; when the thickness is greater than 2.0 mm, there is no effective absorption bandwidth.
[0061] Through the performance analysis of the absorbers obtained in Examples 1-3 and Comparative Example 1, it can be seen that the absorber in Example 2 has the best performance, and its reflection loss value reaches -51.4 dB, achieving strong loss of electromagnetic waves, and has an absorption bandwidth value of up to 7.8 GHz (10.2-18 GHz) at a thickness of 2.5 mm, and the density is only 0.0185 g / cm 3 . It can meet the performance requirements of "thin, light, wide and strong" of ideal absorbing materials. Although the absorber in Example 1 has a relatively wide effective absorption bandwidth, its loss intensity is low and it cannot achieve effective absorption of electromagnetic waves. The reflection loss value of the absorber in Example 3 does not reach -10 dB at all thicknesses and does not have absorbing performance. In addition, when the thickness of the absorber in Comparative Example 1 is less than 2.0 mm, the loss intensity is low and the effective absorption bandwidth is narrow; when the thickness is greater than 2.0 mm, there is no loss capacity at all and it cannot achieve effective absorption of electromagnetic waves.
[0062] The above electromagnetic wave absorption performance shows that the three-dimensional porous structure melamine-titanium carbide @ cobalt nickel composite electromagnetic wave absorption foam material prepared by the present invention has an effective absorption bandwidth of up to 7.8 GHz at a thickness of 2.5 mm; the optimal reflection loss value is -51.4 dB, and it has light weight, broadband and excellent wave absorption performance. In addition, the loss capacity of the composite material to electromagnetic waves can be significantly adjusted by adjusting the concentration of the titanium carbide @ cobalt nickel solution.
[0063] Photothermal performance test of melamine-titanium carbide @ cobalt nickel composite foam material prepared in Example 2: The photothermal performance test of melamine-titanium carbide @ cobalt nickel composite foam material prepared in Example 2 was carried out under 808 nm near-infrared laser light irradiation. The photothermal conversion curve obtained is as follows: Fig.11 and Fig.12 As shown, the thermal image taken by the infrared camera is as follows Fig.13 As shown. Near infrared laser light at 200 mW / cm 2Under the irradiation of light power density, the temperature of composite foam reached 113.6 ℃, which was dynamically adjusted to 25-200 mW / cm 2 The optical power density can effectively control the temperature change of the composite foam and has excellent light-to-heat conversion characteristics.
[0064] Photothermal antibacterial performance test of melamine-titanium carbide @ cobalt nickel composite foam material prepared in Example 2: The antibacterial performance test of the composite foam material prepared in Example 2 was carried out under 808 nm near-infrared laser light irradiation. The antibacterial effect is as follows: Fig.14 Compared with the blank control group, the number of Escherichia coli in the culture dish containing melamine-titanium carbide@cobalt-nickel composite foam material was not significantly reduced when there was no near-infrared laser light irradiation; 2 Under the irradiation of light power density, all Escherichia coli in the culture dish containing melamine-titanium carbide@cobalt-nickel composite foam material were inactivated, showing a strong bactericidal effect and excellent photothermal antibacterial properties.
Claims
1. A melamine-titanium carbide@cobalt-nickel composite foam material, characterized in that: The melamine-titanium carbide@cobalt-nickel composite foam material uses three-dimensional melamine foam as a matrix, and is prepared by compounding titanium carbide and cobalt-nickel metal particles on its surface through vacuum impregnation and electrostatic self-assembly processes.
2. A method for preparing the melamine-titanium carbide@cobalt-nickel composite foam material as claimed in claim 1, characterized in that: The steps include: S1, cleaning and pre-treating the melamine foam, then placing the treated melamine foam in a Tris buffer containing dopamine hydrochloride PDA and stirring, then washing with deionized water for multiple times, and drying for later use; S2, ultrasonically treating the cobalt-nickel particles in a hexadecyltrimethylammonium bromide (CTAB) solution for 30 min, and drying to obtain a cobalt-nickel particle (CTAB) material, stirring the titanium carbide powder and the cobalt-nickel particles (CTAB) in deionized water, ultrasonically treating for 30 min until uniform, and drying to obtain a titanium carbide@cobalt-nickel composite material; S3. Disperse the titanium carbide @ cobalt nickel composite material obtained in S2 in deionized water to obtain a titanium carbide @ cobalt nickel solution, vacuum impregnate the melamine foam obtained in S1 in the titanium carbide @ cobalt nickel solution for 2 h, and dry to obtain a melamine-titanium carbide @ cobalt nickel composite foam material.
3. The method for preparing the melamine-titanium carbide@cobalt-nickel composite foam material according to claim 2, characterized in that: The method for preparing the titanium carbide powder in step S2 comprises the following steps: LiF was dissolved in HCl solution, and then Ti3AlC2 was added. The mixture was stirred at room temperature for 24 h, and centrifuged and washed repeatedly until pH = 6. The precipitate was collected and dispersed in deionized water. Titanium carbide powder was obtained after ultrasonication, centrifugation and drying for 1 h.
4. The method for preparing the melamine-titanium carbide@cobalt-nickel composite foam material according to claim 2, characterized in that: The method for preparing the cobalt-nickel particles in step S2 comprises the following steps: S1. Add Co(NO3)2·6H2O and Ni(NO3)2·6H2O to methanol and stir evenly to form solution A; then dissolve dimethylimidazole and polyvinylpyrrolidone K30 in methanol to form solution B; drop solution B into solution A, stir for 6 h, and obtain CoNi-MOFs precursor after centrifugation and drying; S2. The CoNi-MOFs precursor was pyrolyzed in an argon environment of a tubular furnace at a heating rate of 5 ° / min, kept at 800 °C-900 °C for 2 h, and cooled to obtain cobalt-nickel particles.
5. The method for preparing the melamine-titanium carbide@cobalt-nickel composite foam material according to claim 2, characterized in that: The mass ratio of titanium carbide to cobalt nickel particles (CTAB) in step S2 is 2:
1.
6. The method for preparing the melamine-titanium carbide@cobalt-nickel composite foam material according to claim 2, characterized in that: The concentration of the titanium carbide@cobalt nickel solution in step S3 is 5-20 mg / mL.
7. The method for preparing the melamine-titanium carbide@cobalt-nickel composite foam material according to claim 2, characterized in that: The concentration of the titanium carbide@cobalt nickel solution in step S3 is 10 mg / mL.
8. Use of the melamine-titanium carbide@cobalt-nickel composite foam material as claimed in claim 1 as a light-to-heat conversion material.
9. Use of the melamine-titanium carbide@cobalt-nickel composite foam material as claimed in claim 1 as a photothermal antibacterial material.
10. Use of the melamine-titanium carbide@cobalt-nickel composite foam material as claimed in claim 1 as an electromagnetic wave absorbing material.
Citation Information
Patent Citations
Preparation method of Ni-Co alloy embedded N-doped graphite carbon capsule composite wave-absorbing material
CN110283569A